2007
DOI: 10.1016/j.juro.2007.01.112
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Imidazoquinolines in Urothelial Cell Carcinoma of the Bladder

Abstract: Imidazoquinolines have potent direct activity against bladder cancer cells by decreasing cell viability and inducing apoptosis and cytokine production. In addition, in vivo data suggest antitumor effects in an orthotopic bladder cancer mouse model. Therefore, imidazoquinolines may have therapeutic potential as a synthetic intravesical agent against bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 16 publications
2
69
1
1
Order By: Relevance
“…Several studies have demonstrated that cytokines such as type I IFN or cytotoxic T cells could participate in tumor destruction in vivo induced by imiquimod. Imiquimod can induce a profound tumordirected cellular immune response (17,36). Sullivan et al revealed that antitumorigenic effect of imiquimod is mediated by upregulation of local IFN-α levels (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated that cytokines such as type I IFN or cytotoxic T cells could participate in tumor destruction in vivo induced by imiquimod. Imiquimod can induce a profound tumordirected cellular immune response (17,36). Sullivan et al revealed that antitumorigenic effect of imiquimod is mediated by upregulation of local IFN-α levels (16).…”
Section: Discussionmentioning
confidence: 99%
“…imiquimod can induce direct apoptosis in various cancer cells (13,17,18,20). To investigate whether imiquimod induces apoptosis in prostate cancer cells, TRAMP-C2 cells were treated with 10 or 20 µg/ml of imiquimod for 48 h, stained with PI and Annexin V, and analyzed by flow cytometry.…”
Section: Imiquimod Induces Mitochondria-dependent Apoptosis In Prostamentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown in vitro that imiquimod can directly induce apoptosis of tumor cells using several skin and bladder cancer cells lines, as well as tumor tissue cultures [97][98][99][100][101]. For the skin cancer cell lines, it was demonstrated that this proapoptotic activity was independent of membrane-bound death receptors.…”
Section: Tumor Cellsmentioning
confidence: 99%